Heterogeneity of Liver Disease in Common Variable Immunodeficiency Disorders - Pecoraro, Antonio; Crescenzi, Ludovica; Varricchi, Gilda; Marone, Giancarlo; Spadaro, Giuseppe (Frontiers in Immunology, 2020)
Common variable immunodeficiency (CVID) is the most frequent primary immunodeficiency (PID) in adulthood and is characterized by severe reduction of immunoglobulin serum levels and impaired antibody production in response to vaccines and pathogens. Beyond the susceptibility to infections, CVID encompasses a wide spectrum of clinical manifestations related to a complex immune dysregulation that also affects liver. Although about 50% CVID patients present persistently deranged liver function, burden, and nature of liver involvement have not been systematically investigated in most cohort studies published in the last decades. Therefore, the prevalence of liver disease in CVID widely varies depending on the study design and the sampling criteria. This review seeks to summarize the evidence about the most relevant causes of liver involvement in CVID, including nodular regenerative hyperplasia (NRH), infections and malignancies. We also describe the clinical features of liver disease in some monogenic forms of PID included in the clinical spectrum of CVID as ICOS, NFKB1, NFKB2, CTLA-4, PI3Kδ pathway, ADA2, and IL21-R genetic defects. Finally, we discuss the clinical applications of the various diagnostic tools and the possible therapeutic approaches for the management of liver involvement in the context of CVID.